Human values and selection into supervisory positions: Evidence from nine European countries - Mihails Hazans; Jaan Masso; Per Botolf Maurseth (Global Labor Organization (GLO), 2023)
Do employees with supervisory responsibilities differ from other workers in terms of human values, especially those potentially affecting the quality and efficiency of supervision? This paper uses data from rounds 7-9 of the European Social Survey to examine the selection of employees into supervisory positions in nine Baltic Sea region countries, focusing on ten basic values and four higher order values identified by Schwarz (1992). In eight out of nine countries considered, statistically significant association with supervisory responsibilities is found for three higher order values: positive for Openness to Change and Self-Enhancement but negative for Conservation. By contrast, Self-Transcendence (covering Benevolence and Universalism) is not significantly associated with supervision. In Estonia, Finland, Denmark and (to a smaller extent) Norway and Germany, we find evidence for adverse selection into supervisory jobs based on the Power value posing a risk of autocratic behaviour. When looking at the link between the supervisor's values and the number of subordinates, we find that values that make it easier or harder to become a supervisor tend to work the same way in supervising more workers.
Keywords: D91; J24; M51; P52; 330; supervisory responsibilities; human values; adverse selection; social trust